(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Infectious diseases in children are prevalent due to the relative immaturity of their immune systems and can lead to significant morbidity. Nursing care in pediatric infectious diseases encompasses early detection, appropriate management of therapy, symptom support, infection control, and preventive measures. Pediatric nurses play critical roles in assessing the child’s condition, monitoring vital signs, administering medications on time, implementing isolation and infection prevention protocols, and educating parents on recognizing symptoms, hygiene practices, and immunization importance. Effective prevention strategies, particularly vaccination and hygiene education, are essential for reducing disease incidence. Well-organized nursing care significantly contributes to improving child health outcomes, mitigating disease severity, and preventing complications.